Applying Viewing Techniques in Assisting Learning Listening The Students of Global Prestasi English Center - Suramto Suramto; Episiasi Episiasi; Muhammad Dimas Rizqi; Mardi Murahman; Syafri Aprudi (LP4MK STKIP PGRI Lubuklinggau, 2024)
English listening skill is widely considered fundamental as a basic for further mastering in English. A viewing technique changes into the most suitable option for assisting students in learning listening English. A community service program is implemented to teach listening by using viewing techniques for the students of Global Prestasi English Center. Students are treated with movie-viewing techniques. These include fast forward, silent viewing of language, English learners are assisted to boost listening skills, freeze frame, and partial viewing. It is carried out in fifteen meetings weekday timetable. Students’ responses for the levels of appropriateness are mostly appropriate and absolutely appropriate. These responses are a number student of 93.2% to recognize words meaning, 97.7% to enrich new vocabulary, 86,3% to identify expressions and ideas, 90,9% to improve pronunciation and spelling, 83,1% to recall important words, 81,8% to avoid similar sounds, 93,2% acknowledge to predict or confirm meaning, 93,2% distinguish between sounds, 72,7% understand native speaker accent, and 97,7% listening activity icebreaker.